The Influence of Head of Department on the Performance of State Civil Apparatus Mediated by Work Motivation in the Education Service Kapuas District - Misransyah Akos; Moh. Heru Budihantho; Marce Yansen; Semuel Risal (East Asian Journal of Multidisciplinary Research, 2022)
The type of research used in this research is quantitative research with explanatory research. The research population is all State Civil Apparatus at the Kapuas District Education Office. and samples were drawn using the Probability Sampling technique as many as 42 people using the Slovin formula. The data in this study were collected using questionnaires and interviews. In research data analysis using path analysis techniques. The research results show that study aims to determine (1) the influence of leadership on work motivation (2) the influence of leadership on performance (3) the effect of work motivation on performance, and (4) the influence of leadership on performance mediated by work motivation in the State Civil Apparatus at the Kapuas District Education Office.